Factors influencing acceptance of contract farming among youth - Alby, Jeffrey Lawrence D'Silva; Azman, Azmariana; Abu Samah, Bahaman; Mohamed Shaffril, Hayrol Azril (Universiti Putra Malaysia Press, 2013)

(untitled)
Modern farming methods like contract farming have a great potential in ensuring the sustainability of the agricultural sector. Undoubtedly, youth, being the pillar of society, have an important role in ensuring the survival of agriculture globally. Hence, this study attempts to gauge the level of acceptance of youth towards contract farming and to determine the factors that will have an impact on their level of acceptance. A survey using quantitative methodology was the medium used to collect data from a total number of 400 undergraduates from four tertiary institutions in Malaysia. Data obtained were analysed using the SPSS software. Results showed that the respondents had a high positive acceptance of contract farming while further analysis showed that the significant predictors of acceptance of contract farming were attitude, knowledge and belief. The study also portrayed that education is important in motivating our youth to take up agriculture as a source of livelihood. Relevant exposure to knowledge, information and belief, will enable our youth to participate in the agriculture sector appropriately.